2019
DOI: 10.1111/jzo.12653
|View full text |Cite
|
Sign up to set email alerts
|

Variability and asymmetry in the shape of the spiny dogfish vagina revealed by 2D and 3D geometric morphometrics

Abstract: Genital structures are among the most variable in nature and have been suggested to evolve at exceptionally high rates. However, the vast majority of research on genital morphology has been done on male genitalia. We present one of the few studies of female genital shape using geometric morphometrics, and the first of such studies to employ 3D geometric morphometrics, using the spiny dogfish shark, a taxon for which reproductive biology is well‐studied. In a sample of 21 adult females, we found no correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Thus, unlike for instance (Hedrick et al, 2019), who reported important differences in 2D versus 3D results (e.g., in asymmetric changes, as well as group differences, found only in 3D), we reached almost identical conclusions on patterns of ventral cranial variation in equids using either 2D or 3D analyses. This seems paradoxical given the clearly non-negligible differences in the fine details of inter-individual shape variation (the modest matrix correlations, large R 2 s of 2D-3D differences, and the inaccuracies in phenograms, that we mentioned above).…”
Section: Conclusion: 2d or Not 2d?supporting
confidence: 66%
See 2 more Smart Citations
“…Thus, unlike for instance (Hedrick et al, 2019), who reported important differences in 2D versus 3D results (e.g., in asymmetric changes, as well as group differences, found only in 3D), we reached almost identical conclusions on patterns of ventral cranial variation in equids using either 2D or 3D analyses. This seems paradoxical given the clearly non-negligible differences in the fine details of inter-individual shape variation (the modest matrix correlations, large R 2 s of 2D-3D differences, and the inaccuracies in phenograms, that we mentioned above).…”
Section: Conclusion: 2d or Not 2d?supporting
confidence: 66%
“…Indeed, he found that, although repeatability of 2D data was high for the symmetric component of shape, variability in a specimen orientation introduced important differences in patterns of asymmetric variation in basis capituli of three species of ticks. That asymmetric variation, even when large, may be particularly affected by 2D analyses of pictures, was also suggested by a recent study (Hedrick et al, 2019). The authors employed slightly different landmark configurations to capture the shape of dog-fish vaginas both in 2D and 3D.…”
Section: D To 3d Approximation In Geometric Morphometrics: What Is Tmentioning
confidence: 71%
See 1 more Smart Citation
“…To characterize and quantify genital shape and assess the influence of asymmetry on overall genital shape, we used two-dimensional geometric morphometrics (2DGM) and three-dimensional models of male and female harbor porpoise genitalia. Asymmetry has been previously reported in female genitalia in a wide range of taxa, but can be inconspicuous when present [3][4][5]13,24 . Therefore, we examined the pattern of asymmetry in vaginal folds in both 2D and 3D by generating models of the vaginal lumen, in addition to assessing gross morphology.…”
mentioning
confidence: 77%
“…In these taxa, the lengths of the female common and separate spermathecal ducts are highly divergent among 17 species, and the length of the common spermathecal duct has coevolved with the genital process of males (Kotrba et al, 2014). Several other studies have found similar patterns of female genital diversity and coevolutionary variation between female and male genitalia (Breed, Leigh, & Speight, 2013;Genevcius, Caetano, & Schwertner, 2017;Hedrick, Natanson, Brennan, Antalek-Schrag, & Conith, 2019;Horton & Lewis, 2011;Ilango & Lane, 2000;Ishikawa, 1987;Yoshizawa, Ferreira, Kamimura, & Lienhard, 2014).…”
Section: Sloan and Simmonsmentioning
confidence: 91%